ANALISIS KETIMPANGAN PENDAPATAN DAN POLA PERTUMBUHAN EKONOMI DI WILAYAH BELAJASUMBA TAHUN 2013-2017 - Nazipawati Nazipawati (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2019)
This research attempts to understand income disparity and to identify the pattern of economic growth in Belanjasumba region at 2013-2017 years. The tools of analysis are Williamson Index, Klassen Typology and correlation curve among of economic growth and Williamson Index. Base on Williamson index found that income disparity in Belajasumba region low relative and tended to decreasing. Klassen typology analysis shows that Belajasumba region can be classified into three types: high growth and high income is Jambi, high income but low growth is South Sumatera and Bangka Belitung and high growth but low income is Bengkulu and Lampung. More importantly, findings confirmed that Kuznets hypothesis not could be found in Belajasumba.